A three-layer egg-configurated Bragg microcavity of polyglycerol coated cholesteric-liquid-crystal encapsulated by hollow-glass-microsphere. Issue 4 (15th March 2020) - Hu, Jianyang; Fu, Dongying; Xia, Chunli; Zhang, Chi; Yao, Lishuang; Lu, Chunlian; Sun, Weimin; Liu, Yongjun
ABSTRACT: This letter reports the optical pumped lasing behaviours of a three-layer Bragg resonance cavity consisting of dye-doped cholesteric liquid crystal (DDCLC) microdroplet, polyglycerol-2 and hollow glass microsphere. The function of PG2 is to control the parallel anchoring of the liquid crystal (LC) molecules on the surface of the LC microdroplet. The whispering-gallery mode (WGM), radial Bragg (photonic bandgap, PBG) mode and Bragg WGM (BWGM) are observed in DDCLC microspheres with different helical pitches and LC refractive indices. The formation mechanisms of six types of lasing emission conditions are analysed in detail. The study results present the prospect of controlling the output mode of the laser. Furthermore, such solid shell-based DDCLC microspheres have outstanding potential applications in miniaturised 3D Bragg lasers, sensors, and integrated and tunable optical devices. GRAPHICAL ABSTRACT: